Blowup and Self-Similar Solutions for Two-Component Drift-Diffusion Systems - Guerra-Benavente, I (2012)
We discuss asymptotic properties of solutions of two-component parabolic drift-diffusion systems coupled through an elliptic equation in two space dimensions. In particular, conditions for finite time blowup versus the existence of forward self-similar solutions are studied. © 2012 Elsevier Ltd. All rights reserved.